Mechanism of Body Weight Reducing Effect of Oral Boric Acid Intake. (3rd June 2013) - Aysan, Erhan; Sahin, Fikrettin; Telci, Dilek; Erdem, Merve; Muslumanoglu, Mahmut; Yardımcı, Erkan; Bektasoglu, Huseyin
Abstract : Objective . The effect of oral boric acid intake on reducing body weight has been previously demonstrated although the mechanism has been unclear. This research study reveals the mechanism. Subjects . Twelve mice were used, in groups of six each in the control and study groups. For five days, control group mice drank standard tap water while during the same time period the study group mice drank tap water which contains 0.28 mg/250 mL boric acid. After a 5-day period, gene expression levels for uncoupling proteins (UCPs) in the white adipose tissue (WAT), brown adipose tissue (BAT), and skeletal muscle tissue (SMT) and total body weight changes were analyzed. Results . Real time PCR analysis revealed no significant change in UCP3 expressions, but UCP2 in WAT (P : 0.0317), BAT (P : 0.014), and SMT (P : 0.0159) and UCP1 in BAT (P : 0.026) were overexpressed in the boric acid group. In addition, mice in the boric acid group lost body weight (mean 28.1%) while mice in the control group experienced no weight loss but a slight weight gain (mean 0.09%, P < 0.001 ). Conclusion . Oral boric acid intake causes overexpression of thermogenic proteins in the adipose and skeletal muscle tissues. Increasing thermogenesis through UCP protein pathway results in the accelerated lipolysis and body weight loss.